Surgical Out Come of Extradural Haematoma Patients at Department of Neurosurgery in Chittagong Medical College Hospital: A Study of 30 Patients - Debnath, Haradhan; Rahman, M Lutfor; or-Rashid, Harun (TAJ: Journal of Teachers Association, 2009)
Bleeding of extradural space is called extradural haematoma. This was a prospective study. In this study included 30 patients of extradural haematoma. Mean age of patients was 29 ±15year. 26(83.3%) of patients were male and 5(16.6%) of patients were female. Commonest cause of haematoma were road traffique accidents. Among them 28(93.3%) patients were treated by surgical procedure and 2(6.6%) were treated by conservative procedure. After surgery among the 30 patients 26(83.3%). patients were fully recovered. Postoperatively two patients recovered with disabilities (one had visual field defect and one had Psychological disturbance). Two patients (6.6%) died on 3rd and 6th post operative day respectively due to aspiration pneumonia. Mortality and morbidity were more among those who were operated after 48 hours of occurrence. So, this study concluded that the early surgery is more life saving than the late surgery. doi: 10.3329/taj.v20i2.3075 TAJ 2007; 20(2): 136-139